1998
DOI: 10.1002/chin.199822083
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Sulfonic Acid Functionalized Ordered Mesoporous Materials as Catalysts for Condensation and Esterification Reactions.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…PFS nanoparticles gave a higher hydronium ion load (1.7 mmol H + /g) than the AS and BCOOH nanoparticles at 0.9 and 0.2 mmol H + /g, respectively. The acid capacity values of PFS and AS agree with the values previously reported in the literature [28,[41][42][43][44][45]. AS nanoparticles had a larger sulfur content (4.9%) than PFS nanoparticles (3.1%).…”
Section: Acid and Organic Incorporationsupporting
confidence: 89%
See 1 more Smart Citation
“…PFS nanoparticles gave a higher hydronium ion load (1.7 mmol H + /g) than the AS and BCOOH nanoparticles at 0.9 and 0.2 mmol H + /g, respectively. The acid capacity values of PFS and AS agree with the values previously reported in the literature [28,[41][42][43][44][45]. AS nanoparticles had a larger sulfur content (4.9%) than PFS nanoparticles (3.1%).…”
Section: Acid and Organic Incorporationsupporting
confidence: 89%
“…Aggregation of PFS nanoparticles could have decreased the available area for catalytic hydrolysis also. Likewise, AS nanoparticles are difficult to disperse in aqueous solutions which could be explained by the poor water affinity of AS and PFS functionalized materials [44,48]. Higher cellobiose conversion could be attained with this catalyst if a better dispersion is achieved.…”
Section: Cellobiose Hydrolysismentioning
confidence: 98%
“…However, low catalytic activity could have been a consequence of the poor water affinity observed for this catalyst. These results agree with the findings of Van Rhijn et al (1998) and Bootsma and Shanks (2007). Gill et al (2007) and Suganuma et al (2008) reported that acid groups in the PFS nanoparticles were leached into the reaction solution.…”
Section: Performance Of the Catalystssupporting
confidence: 91%
“…To increase the contact area between mesoporous materials and substrates for high conversion yield and efficiency, the present work proposes use of acidfunctionalized nanoparticles for treatment of cellulosic materials. Extensive studies have also been reported on the synthesis and evaluation of mesoporous silicas functionalized with acid groups (Harmer et al 1996;Harmer et al 1998;Van Rhijn 1998;Corma et al 2004;Alvaro 2005;Rac et al 2006;Harmer et al 2007). Monodisperse materials have an advantage that provides large surface areas.…”
Section: Acid Strength Of Sulfonic Supported Acidsmentioning
confidence: 99%
“…For example, mesoporous silica having thiol groups on the pore surface showed high adsorption efficiency for heavy metals such as Hg, Ag, and Cd ions [ 80 , 81 ]. Sulfonic acid groups grafted onto mesoporous materials, as another example, exhibited high catalytic activity for selective formation of bulky organic molecules [ 82 ].…”
Section: An Overview Of Modification Of As-synthesized Mcm-41mentioning
confidence: 99%